Pengaruh Nilai-Nilai Inti Perusahaan, Kompetensi Karyawan, dan Gaya Kepemimpinan Terhadap Kinerja Karyawan di PT Arkana Solusi Digital (Indo-MathEdu Intellectuals Journal, 2025)
This research analyzes the influence of corporate core values, employee competencies, and leadership styles on employee performance at PT Arkana Solusi Digital (Arkana), an IT service company in Indonesia. This study uses a quantitative approach with descriptive and verificative methods, as well as a cross-sectional study design. The research population is all employees of Arkana in Jakarta, with 63 respondents participating. Data were collected through questionnaires and analyzed using multiple linear regression. The research results indicate that simultaneously, the company's core values, employee competencies, and leadership style have a positive and significant effect on employee performance, with a coefficient of determination (R²) of 0.575, which means 57.5% of the variation in employee performance can be explained by these three variables. However, partially, the company's core values do not have a significant effect on employee performance (p=0.374), which indicates that the internalization of these values has not been optimal. In contrast, employee competencies (p < 0.001) and leadership style (p = 0.009) have a significant and positive effect on employee performance.